2014
DOI: 10.1098/rspb.2014.1078
|View full text |Cite
|
Sign up to set email alerts
|

Three-way interactions between mosquito population, viral strain and temperature underlying chikungunya virus transmission potential

Abstract: Interactions between pathogens and their insect vectors in nature are under the control of both genetic and non-genetic factors, yet most studies on mosquito vector competence for human pathogens are conducted in laboratory systems that do not consider genetic and/or environmental variability. Evaluating the risk of emergence of arthropod-borne viruses (arboviruses) of public health importance such as chikungunya virus (CHIKV) requires a more realistic appraisal of genetic and environmental contributions to ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
157
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 49 publications
(88 reference statements)
1
157
3
Order By: Relevance
“…When A. albopictus transmission potential for CHIKV was measured in 6 worldwide vector populations, with 2 virus strains and in 2 ambient temperatures (20°and 28°C), strong effects of the 3-way interaction of mosquito population, virus strain, and temperature were observed. This highlights the importance of studies that focus on genotype by genotype by environment interactions [43]. Differences in transmission efficiency of CHIKV by A. aegypti and A. albopictus were noted in populations of both species from the Americas, while dissemination rates were similar.…”
Section: Vector Competencementioning
confidence: 88%
“…When A. albopictus transmission potential for CHIKV was measured in 6 worldwide vector populations, with 2 virus strains and in 2 ambient temperatures (20°and 28°C), strong effects of the 3-way interaction of mosquito population, virus strain, and temperature were observed. This highlights the importance of studies that focus on genotype by genotype by environment interactions [43]. Differences in transmission efficiency of CHIKV by A. aegypti and A. albopictus were noted in populations of both species from the Americas, while dissemination rates were similar.…”
Section: Vector Competencementioning
confidence: 88%
“…The GÂG principle was extended to integrate the interplay of environmental factors resulting in GÂGÂE (genotypeby-genotype-by-environment) [118,119]. Temperature is one of the best-studied factors affecting HT competency.…”
Section: Temperaturementioning
confidence: 99%
“…The study demonstrated that these sources of variation do not necessarily act independently and may interact with each other (mosquito genotype × virus genotype × environment) to determine the outcome of VC. 60 To accurately assess the impact and plasticity of Wolbachia-mediated DENV blocking, it is also necessary to take this G × G × E interaction into consideration.…”
Section: Discussionmentioning
confidence: 99%